A potential paradigm shift in global mobility? the impact of the COVID-19 pandemic - Mello, Rodrigo; Erro-Garces, Amaya; Dickmann, Michael; Brewster, Chris (Elsevier, 2023)
The COVID-19 pandemic profoundly affected the global mobility (GM) policies of multinational enterprises (MNEs). Through interviews with policy decision-makers in 32 companies, we applied Interpretative Phenomenological Analysis to examine how the pandemic accelerated changes in MNE policies and the management of GM. Our framework builds on contingency theory, traditionally concerned with aligning organizational policies with macro- and meso-level contextual factors. We extend this by integrating micro-level individual variables, such as career aspirations and well-being, as contingent factors influencing GM practices. There is variation in GM responses in relation to the volume of GM activities, GM-related policies, investments in digitalization and technology, and variations in mobility types. We observed a potential paradigm shift that affords employees greater agency in their global mobility paths, thereby greater granularity to contingency theory. This nuanced approach opens new research avenues and equips organizational leaders with a comprehensive set of variables for GM decision-making. Our findings indicate lasting global mobility changes but foresee gradual implementation due to associated risks.
Keywords: Global mobility; Pandemic; Virtual working; IHRM policies; Contingency theory